Cancer, ageing, multimorbidity and primary care. (11th May 2017) - Mazza, D.; Mitchell, G.
Abstract : Cancer care is complex, and made more so by multimorbidity and ageing. Multimorbidity affects all stages of cancer care from prevention and early detection through to end of life care. The effectiveness of cancer treatments in multimorbid patients may not be understood, as many conditions common in older people may be exclusion criteria in oncology clinical trials. The interaction between pre‐existing physical capacity, multiple medical conditions and ageing can delay diagnosis, impact on treatments, complicate survivor care, and impact on decisions about starting and ceasing treatments. General Practitioners (GPs) manages multimorbidity routinely, yet the GP role in comprehensive cancer care is limited. Integration of GP management of multimorbidity in conjunction with oncology services should improve patient outcomes. Integration of care for these patients can educate patients on the minimisation of multimorbidity, develop personalised screening plans and contribute to the wholistic management of people in the surveillance period. GPs should have a major role in end of life care. Integration of general practice and oncology should benefit patient care.